ВИКОРИСТАННЯ ҐЕНДЕРНО ЗБАЛАНСОВАНОГО МАТЕРІАЛУ ПІД ЧАС ВИКЛАДАННЯ ІСТОРІЇ УКРАЇНИ - Христенко, Ольга (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті репрезентовано модель впровадження ґендерного підходу в процес викладання навчальної дисципліни «Історія України». За допомогою методів історико-ретроспективного, порівняльного аналізу та контент-аналізу виявлено конкретні історичні проблеми, котрі потребують доповнення новітніми даними про суспільну діяльність видатних жінок та жіночих організацій. Розроблено низку навчальних тем і питань, що висвітлюють роль жінок в історичному розвитку суспільства. Обґрунтовано доцільність використання ґендерно збалансованого матеріалу під час вивчення тем про громадські, політичні, визвольні рухи в Україні, становлення української державності у ХХ столітті, Голодомор 1932–1933 років, розвиток освіти та культури. Запропоновано приклади гендерно збалансованого навчального матеріалу в контексті вивчення проблематики просвітницького руху в Україні. В статье представлеа модель внедрения гендерного подхода в процесс преподавания учебной дисциплины «История Украины». С помощью методов историко-ретроспективного, сравнительного анализа и контент-анализа выявлены конкретные исторические проблемы, которые нуждаются в дополнении новейшими данными об общественной деятельности выдающихся женщин и женских организаций. Разработан ряд учебных тем и вопросов, представляющих роль женщин в историческом развитии общества. Обоснована целесообразность использования гендерно сбалансированного материала при изучении тем об общественных, политических, освободительных движениях в Украине, становление украинской государственности в ХХ веке, Голодомор 1932–1933 годов, развитие образования и культуры. Предложено примеры гендерно сбалансированного учебного материала в контексте изучения проблематики просветительского движения в Украине. In the article is represented a model of implementing of the gender approach in the process teaching of the educational subject «History of Ukraine». Employing the methods of historical-retrospective, comparative analysis and content analysisб detected the concrete historical problems, that need to additions to the latest data on public activity of prominent women and women’s organizations. Several educational themes and issues that reveal the role of women in the historical development of society were developed. Advisability of using gender balanced material when studying of topics about civil, political, liberation movement in Ukraine, the formation of the Ukrainian state in the twentieth century, the Famine of 1932–1933, development of education and culture has been proven. Examples of gender-balanced educational material in the context of the study of the educational movement in Ukraine have been proposed. So, in considering of the Famine, it is necessary to acquaint the students with the educational activities of the Ukrainian National Women’s Council led by Milena Rudnytska, speaking in defense of Ukrainian hungry during a meeting of the League of Nations. Also it has been presented the relevant examples of gender-balanced teaching material in the context of historical problems which are studied in high school.